Equity: A maternal and neonatal problem - Farha, Mst Nahid; Kuddus, Abdul (Indian Journal of Child Health, 2018)
This paper highlights the maternal and neonatal mortality within the developing countries in Asia and South Africa to include a discussion on how maternal and neonatal mortality is a serious problem in developing nations. The study also draws strategies to reduce maternal and neonatal problem.